Convenience Space Planning For Secondary Education In Delta State - Kenkel, Padre (Advances in Social Sciences Research Journal, 2019)
The study was on convenience planning in the provision of secondary education in Delta State. It adopted the descriptive survey design. The population was all the 891 secondary schools in the state. Through stratified random sampling technique, a sample size of225 schools was drawn (public -115, private -110). A checklist was used to obtain data for the study. The data generated were analysed using percentage. The study revealed that convenience space was adequately planned in both public and private secondary schools, though with minor differences in some areas. The study recommended that they should be a collaborative framework between the ministry of education and the schools both public and private to ensure strict compliance with convenience space specified standards. This will help improve those areas where there are deficiencies in convenience space planning.